Gonadal failure is associated with visceral adiposity in myotonic dystrophies. (1st June 2015) - Passeri, Elena; Bugiardini, Enrico; Sansone, Valeria A.; Pizzocaro, Alessandro; Fulceri, Cinzia; Valaperta, Rea; Borgato, Stefano; Costa, Elena; Bandera, Francesco; Ambrosi, Bruno; Meola, Giovanni; Persani, Luca; et al.
Abstract Background Hypogonadism occurs in myotonic dystrophies type 1 (MD1) and type 2 (MD2). Sertoli and Leydig cell secretions, including insulin‐like peptide‐3 (INSL3), anti‐Müllerian hormone (AMH) and inhibin B, were evaluated in male patients with MD. Design Academic settings. Forty‐four male patients with MD [31 MD1, 13 MD2, aged 59 (50–64) years, median (interquartile range)], age‐, sex‐ and BMI‐matched non‐MD hypogonadal patients (n = 14) and healthy controls (n = 32). Serum FSH, LH, inhibin B, AMH, testosterone (T) and INSL3 were measured; fat and muscle masses were evaluated by DEXA. Results Overt primary hypogonadism occurred in 29% of patients with MD1 and 46% of patients with MD2. Considering subclinical forms, the prevalence increased to 69% of MD1 and 100% of MD2. A half of patients with MD experienced symptoms. INSL3 levels were unaffected in most patients with MD. By contrast, AMH and inhibin B were reduced in most patients with MD and unrelated to age. Patients with MD showed increased body and visceral fat. Free T levels were negatively predicted by fat mass, and AMH and FSH levels were negatively correlated with waist/hip ratio and fat mass. AMH, inhibin B and FSH levels positively correlated with muscle strength and muscle mass. Conclusions AMH and inhibin B secretion failures are common in male patients with MD and are more severe than Leydig cell hormones impairment. AMH and inhibin B measurements might provide clinical utility in evaluating fertility in patients with MD. Serum T, AMH and inhibin B productions are negatively influenced by increased fat mass, while AMH and inhibin B might be markers of muscle impairment.